(untitled) (Research, Society and Development, 2021)
Violence and criminality are not only present in large cities and metropolitan regions, but in all areas that are precarious in social conditions, thus requiring an understanding of the characteristics and impacts of crime and violence in Brazilian cities. The objective of the study is to assess crime in the State of Pará, Brazil, in the years 2017 to 2019. It is a quantitative exploratory study carried out in the 144 municipalities in the State of Pará, Brazil. The crime data: (i) theft; (ii) robbery; (iii) vehicle robbery; (iv) homicide; (v) robbery-homicide and (vi) bodily injury followed by death, which occurred in Pará, Brazil, were extracted from Police Reports. Population data were obtained through the Brazilian Institute of Geography and Statistics. To measure violent crime in the municipalities of Pará, Brazil, the Standardized Double-Weighted Bayesian Average Crime Index for Municipalities was used, and for the spatial presentation of the results, Geographic Information Systems were used. It was found that most municipalities had low or very low crime rates in 2019. It was also found that the top 5 placed in the 2018 and 2019 ranking had very high crime rates. However, in 2019, only one municipality had a very high rate. It was possible to assess the distribution of crime in the municipalities of Pará, Brazil, thus achieving the objective of the study. It is hoped that the results will assist the public security organs of the state in the elaboration of effective actions in the municipalities most affected by crime.